Social and Ethical Aspects of Biometrics - Despotidis, Konstantinos (Bioethica, 2022)
As technology is constantly evolving, so has the science of biometrics. Biometrics is the science that studies and examines the recognition and identification of individuals based on their physical or behavioral characteristics. Sequentially, biometric systems accurately validate the authenticity of these characteristics of individuals resulting in a variety of applications. However, there are ethical and social issues regarding the management of biometric data. Examples are the privacy, autonomy, transparency, and social exclusion of people from diverse groups, as it is, for example, the elderly population. Similar questions are being asked about how the biometric data of refugees are being used by various organizations and governments that have upgraded border identification systems for the sake of upgraded security. Therefore, while the science of biometrics has contributed to the improvement of the standard of living and safety of people, providing solutions to many problems, it has also been the subject of debate on whether it violates human rights.